Simple flow injection system for non-enzymatic glucose sensing based on an electrode modified with palladium nanoparticles-graphene nanoplatelets/mullti-walled carbon nanotubes. (10th October 2019) - Promsuwan, Kiattisak; Kachatong, Napada; Limbut, Warakorn
Abstract: This work presents a novel flow injection-based non-enzymatic glucose sensor that uses an electrode modified with a nanocomposite of mullti-walled carbon nanotubes wrapped with palladium nanoparticle-graphene nanoplatelets (PdNPs-GNPs/MWCNTs). The nanocomposite was prepared using a reducing agent and ultra-sonication. A glassy carbon electrode (GCE) was modified by drop casting a suspension of the nanocomposites onto the electrode, which was dried in 5 min at 70 °C. The modified electrode exhibited strong catalytic activity for glucose oxidation at a low working potential (−0.10 V). The linear range of detection was wide (0.025–10 and 10–100 mM) and the system showed good sensitivity (83.0 and 52.9 μA mM −1 cm −2 ) with a low limit of detection (0.008 mM). Repeatability (RSD < 4.7%, n = 20), reproducibility (RSD = 1.4%, n = 6) and operational stability (116 injections per electrode, RSD = 3%) were good at high sample throughputs (60 samples hour −1 ). Selective response to glucose was excellent in the presence of physiological levels of interferences commonly found in human blood. Glucose was detected with an RSD below 4% and recovery between 97 ± 4% and 99 ± 4%: comparable results to those obtained from standard hexokinase-spectrophotometric detection. The analytical performance of the sensor was suitable for routine analysis of glucose and other analytes. Graphical abstract: Image 10333 Highlights: A novel flow injection-based non-enzymatic glucose sensor using PdNPs-GNPs/MWCNTs/GCE. . PdNPs-GNPs/MWCNTs nanocomposite was successfully prepared by a simple strategy. Prepared nanocomposite was used in a flow-based non-enzymatic glucose sensor. Results showed no significant difference to conventional analysis ( P > 0.05). The fabricated sensor is a potential candidate for routine glucose analysis.